Nano-Strategies to Fight Multidrug Resistant Bacteria—“A Battle of the Titans” - Baptista, Pedro V.; McCusker, Matthew P.; Carvalho, Andreia; Ferreira, Daniela A.; Mohan, Niamh M.; Martins, Marta; Fernandes, Alexandra R. (Frontiers in Microbiology, 2018)
Infectious diseases remain one of the leading causes of morbidity and mortality worldwide. The WHO and CDC have expressed serious concern regarding the continued increase in the development of multidrug resistance among bacteria. Therefore, the antibiotic resistance crisis is one of the most pressing issues in global public health. Associated with the rise in antibiotic resistance is the lack of new antimicrobials. This has triggered initiatives worldwide to develop novel and more effective antimicrobial compounds as well as to develop novel delivery and targeting strategies. Bacteria have developed many ways by which they become resistant to antimicrobials. Among those are enzyme inactivation, decreased cell permeability, target protection, target overproduction, altered target site/enzyme, increased efflux due to over-expression of efflux pumps, among others. Other more complex phenotypes, such as, biofilm formation and quorum sensing do not appear as a result of the exposure of bacteria to antibiotics although, it is known that biofilm formation can be induced by antibiotics. These phenotypes are related to tolerance to antibiotics in bacteria. Different strategies, such as the use of nanostructured materials, are being developed to overcome these and other types of resistance. Nanostructured materials can be used to convey antimicrobials, to assist in the delivery of novel drugs or ultimately, possess antimicrobial activity by themselves. Additionally, nanoparticles (e.g. metallic, organic, carbon nanotubes, etc.) may circumvent drug resistance mechanisms in bacteria and, associated with their antimicrobial potential, inhibit biofilm formation or other important processes. Other strategies, including the combined use of plant-based antimicrobials and nanoparticles to overcome toxicity issues, are also being investigated. Coupling nanoparticles and natural-based antimicrobials (or other repurposed compounds) to inhibit the activity of bacterial efflux pumps; formation of biofilms; interference of quorum sensing; and possibly plasmid curing, are just some of the strategies to combat multidrug resistant bacteria. However, the use of nanoparticles still presents a challenge to therapy and much more research is needed in order to overcome this. In this review, we will summarize the current research on nanoparticles and other nanomaterials and how these are or can be applied in the future to fight multidrug resistant bacteria.